Comprehensive Genotyping in Two Homogeneous Graves' Disease Samples Reveals Major and Novel HLA Association Alleles - Chen, Pei-Lung; Fann, Cathy Shen-Jang; Chu, Chen-Chung; Chang, Chien-Ching; Chang, Su-Wei; Hsieh, Hsin-Yi; Lin, Marie; Yang, Wei-Shiung; Chang, Tien-Chun (PloS one, 2011)
Graves' disease (GD) is the leading cause of hyperthyroidism and thyroid eye disease inherited as a complex trait. Although geoepidemiology studies showed relatively higher prevalence of GD in Asians than in Caucasians, previous genetic studies were contradictory concerning whether and/or which human leukocyte antigen (HLA) alleles are associated with GD in Asians. We conducted a case-control association study (499 unrelated GD cases and 504 controls) and a replication in an independent family sample (419 GD individuals and their 282 relatives in 165 families). To minimize genetic and phenotypic heterogeneity, we included only ethnic Chinese Han population in Taiwan and excluded subjects with hypothyroidism. We performed direct and comprehensive genotyping of six classical HLA loci (HLA-A, -B, -C, -DPB1, -DQB1 and -DRB1) to 4-digit resolution. Combining the data of two sample populations, we found that B*46:01 (odds ratio under dominant model [OR]  = 1.33, Bonferroni corrected combined P [P(Bc)]  = 1.17 x 10⁻²), DPB1*05:01 (OR  = 2.34, P(Bc) = 2.58 x 10⁻¹⁰), DQB1*03:02 (OR  = 0.62, P(Bc)  = 1.97 x 10⁻²), DRB1*15:01 (OR  = 1.68, P(Bc) = 1.22 x 10⁻²) and DRB1*16:02 (OR  = 2.63, P(Bc)  = 1.46 x 10⁻⁵) were associated with GD. HLA-DPB1*05:01 is the major gene of GD in our population and singly accounts for 48.4% of population-attributable risk. These GD-associated alleles we identified in ethnic Chinese Hans, and those identified in other Asian studies, are totally distinct from the known associated alleles in Caucasians. Identification of population-specific association alleles is the critical first step for individualized medicine. Furthermore, comparison between different susceptibility/protective alleles across populations could facilitate generation of novel hypothesis about GD pathophysiology and indicate a new direction for future investigation.